A Review on Chukkumthippalyadi Gulika: A Potent Herbo-Mineral Formulation in Jwara - Lakshmi P N; Sreeni T V (International Journal of Ayurveda and Pharma Research, 2022)
Rasa Shastra is a branch which deals with mercury, metals, minerals, gems, herbal drugs and various principles of alchemy and metallurgy. The popular books on Kerala Ayurvedic treatment like Sahasrayoga and Chikitsamanjari describes various potent herbomineral formulations. One such Kharaleeya rasayana yoga is Chukkumthippalyadi gulika explained in Jwaraprakarana of Chikitsamanjari. This Yoga has a wide range of therapeutic utility and indicated in Tridoshaja sannipathika jwara. Jwara is the first and the most serious of all diseases so it needs to be specially attended. Ingredients in the formulation include drugs from Maharasa, Uparasa and Sadharana rasa vargikarana of Rasa dravyas which are to be used in the formulation after proper Samskaras like Sodhana and Marana. Few other controversial drugs like Gandhamarjaraveerya, and Mrigasringa are also included in the formulation. Other herbal ingredients include Sunti, Pippali, Bola, Vacha, Jeeraka, Rudraksha, Kiratatikta and Karpoora. Indication of the Yoga specifies Haret Drak Sannipathajwaram depicts its immediate action on Jwarachikitsa. Aims and Objective: The main objective of this article is to discuss the therapeutic uses of Chukkumthippalyadi gulikaand to discuss the different pharmacological properties and therapeutic uses of isolated constituent drugs of Chukkumthippalyadi gulika thus to raise an awareness of this particular formulation in the healthcare system so that they can be applied to community needs. Discussion: Most of the drug in Chukkumthippalyadi gulika is Katu, Tikta rasatmak with Ushna Veerya, Laghu, Ruksha, and Tikshna Gunatmak having Jwarghna property. Conclusion: Chukkumthippalyadi gulika is a very effective drug, it has multidimensional broad spectrum activity so this can be used in all type of Jwara.